Respuesta :
Answer:
n = 3
Step-by-step explanation:
-1(n2 + 3) if n = -3.
from the question
-1(n2 + 3)
we are then asked to find n if its equals to -3
solution
-1(n2 + 3) .................. we are going to open the bracket with-1 according to BODMAS rule
we have,
-n²-3
when the value of n = -3
we have,
= (-3)² - 3
= 9 - 3
= 3
therefore when n = -3 in the expression -1(n2 + 3) the value of n = 3
to check if your answer is correct you will put the value of n which is 3 into the -1(n2 + 3) then you will see that the right handside = lefthandside
which is
3=3...........proved.